Clinical efficacy of Bupleurum inula flower soup for immune damage intervention in Hashimoto’s thyroiditis: A placebo-controlled randomized trial - Meng, Xiangfei; Liu, Shiyi; Deng, Xiumin; Li, Xintong; Lei, Jia; Jiang, Hongye; Liu, Mengyao; Zhang, Ning; Liu, Shiwei (Frontiers in Pharmacology, 2022)
Background: Antibody-mediated humoral immune response is involved in the damage process in Hashimoto’s thyroiditis (HT). Although the traditional Chinese medicine (TCM) formula bupleurum inula flower soup (BIFS) is often used in HT treatment, it has not been evaluated through high-quality clinical research. Rigorously designed randomized, double-blind, prospective clinical studies are urgently needed to evaluate BIFS for intervening in the HT immune damage process, and to improve clinical prognosis and patient quality of life. Methods: A prospective randomized, double-blind, placebo-controlled trial was used to evaluate the efficacy of BIFS. Fifty participants diagnosed with HT with hypothyroidism were randomly assigned at a 1:1 ratio to the BIFS (levothyroxine with BIFS) or control (levothyroxine with placebo) group. Participants received eight weeks of treatment and were followed for 24 weeks. They were monitored for: levels of thyroid peroxidase antibody (TPOAb), thyroglobulin antibody (TgAb), and thyroid stimulating hormone (TSH); scores for depression, anxiety, and health-related quality of life (HRQoL); thyroid volume; safety indicators including routine blood tests, liver and kidney functions, and electrocardiogram; and levothyroxine dose. Results: Forty-eight participants completed the study and were included in the final analysis. At baseline, there were no significant between-group differences in the observed indicators (P>0.05). Post-treatment, compared with the control group, the BIFS group had significantly lower levels of TPOAb (275.77±132.98 vs 441.78±195.50, P=0.001), TgAb (385.92±281.91 vs 596.17±282.26, P=0.013), and TSH (6.57±3.73 vs 9.63±5.34, P=0.001). Compared with the control group, the BIFS group’s scores improved significantly for depression (47.00±5.12 vs 51.04±3.22, P=0.002), anxiety (43.21±4.22vs 48.08±2.81, P=0.005), and HRQoL physical (62.08±5.97 vs 57.96±4.71, P=0.011) and psychological (60.17±5.94 vs 55.75±7.09, P=0.024) subscores. At 24-week follow-up, levothyroxine combined with TCM allowed a significantly reduced levothyroxine dose (0.58±0.43 vs 1.02±0.45, P=0.001). The post-treatment clinical efficacy rates differed significantly (P=0.03), with 75% (18/24) for the BIFS group and 46% (11/24) for the control group. There were no significant between-group differences in thyroid volume or safety indicators after eight treatment weeks or at the 24-week follow-up (P>0.05). Conclusions: The TCM BIFS can effectively reduce thyroid titer, relieve clinical and emotional symptoms, and improve HRQoL in patients with HT.